Nerve block with alkalinized local anaesthetics: a clinical comparative study - Baruah, Minoti (International Journal of Research in Medical Sciences, 2017)
Background: A number of clinical studies have been performed in an attempt to establish the effects of alkalinization on potency of local anesthetics. A clinical comparative study was carried out to evaluate to study the effect of alkalinizing lignocaine, bupivacaine and their alkalinized counter parts for brachial plexus blockade. Methods: A clinical comparative study was done on 100 patients in the Orthopedic and General Surgery operation theaters of Gauhati Medical College Hospital, Guwahati, India during the period from November 1997 to October 1998. Patients were divided into 4 groups of 25 each. The four drugs were lignocaine, bupivacaine and their alkalinized counter parts. The supraclavicular approach to the brachial plexus was used. Results: The study observed a reduction in the latency of onset of surgical anaesthesia by both alkalinized lignocaine and bupivacaine. The effect of lignocaine being more pronounced at 44.26% against 33.9% of bupivacaine. Alkalinization of both lignocaine and bupivacaine enhanced the quality of sensory block as well as improved the quality of motor block. Conclusions: From present study, we conclude that addition of sodium bicarbonate to commercially available local anaesthetic solutions enhances the quality of local anaesthetics, by a quicker onset of action, more profound sensory and motor block.